Practical reflections on the international judicial jurisdiction and the filiation - Sánchez Cano, María Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
As of today, there is no regulation in European private International Law that regulates filiation by nature, which is why the Spanish Courts will resolve disputes that arise, applying our rules of private International Law of internal production. This paper will examine the problems raised in practice by the application of the forums provided for in article 22. quater. d) LOPJ, on which the determination of the international judicial competence of the Spanish Courts in matters of filiation depends. To this end, the Order of the Provincial Court of Oviedo of February 13, 2020 will be taken as the starting point.